2000
DOI: 10.1021/bi001850u
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Model System for Processive Phosphorylation by Src Family Kinases

Abstract: The Src homology 2 (SH2) and Src homology 3 (SH3) domains of Src family kinases are involved in substrate recognition in vivo. Many cellular substrates of Src kinases contain a large number of potential phosphorylation sites, and the SH2 and SH3 domains of Src are known to be required for phosphorylation of these substrates. In principle, Src could phosphorylate these substrates by either a processive mechanism, in which the enzyme remains bound to the peptide substrate during multiple phosphorylation events, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 34 publications
8
45
0
Order By: Relevance
“…As recently demonstrated, the interaction of the p60 src SH3 domain with the ligand sequence of the substrate is important for activation of the catalytic domain and autophosphorylation (41), and the addition of an SH3 domain ligand to a substrate peptide increases its phosphorylation 10-fold via lowering of the K m value of the substrate and kinase activation (42). Thus, putative SH3-and SH2-binding domains present in MLCK-1 N-terminal portion (Fig.…”
Section: Identification Of P60mentioning
confidence: 73%
“…As recently demonstrated, the interaction of the p60 src SH3 domain with the ligand sequence of the substrate is important for activation of the catalytic domain and autophosphorylation (41), and the addition of an SH3 domain ligand to a substrate peptide increases its phosphorylation 10-fold via lowering of the K m value of the substrate and kinase activation (42). Thus, putative SH3-and SH2-binding domains present in MLCK-1 N-terminal portion (Fig.…”
Section: Identification Of P60mentioning
confidence: 73%
“…Src kinases preferentially phosphorylate peptide substrates containing SH3 ligands (41), but ACK1 showed no activity toward these peptides, although ACK1 is able to bind to the SH3-binding substrate ( Fig. 2A).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we included a substrate that possesses an SH3 domain-binding polyproline sequence. For Src family kinases, the addition of an SH3 domain ligand to a substrate increases its phosphorylation by activating down-regulated kinase and by decreasing substrate K m (41). The purified ACK1 kinase-SH3-CRIB construct clearly preferred the Abl substrate from this group of peptides ( Fig.…”
Section: Purification Of Ack1 and Characterization Of Substratementioning
confidence: 91%
“…Distributive phosphorylation of MAPKs is important for establishing, for example, the switch-like response observed in Xenopus oocytes in response to progesterone [45]. In the case of processive phosphorylation, Mayer et al first showed that Src homology 2 (SH2) domains promote hyperphosphorylation of substrates by tyrosine kinases [46], and subsequent model experiments confirmed that Src family kinases can phosphorylate substrates containing an SH2 domain ligand in a processive manner [47]. In this review, we discuss specific examples of proteins that undergo a processive mechanism of multisite phosphorylation.…”
Section: Multisite Phosphorylation By a Single Protein Kinasementioning
confidence: 99%